2012
DOI: 10.1111/j.1460-9568.2012.08087.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of spinal TDAG8 and its downstream PKA signaling pathway contribute to bone cancer pain in rats

Abstract: Bone cancer pain is difficult to treat and has a strong impact on the quality of life of patients. Few therapies have emerged because the molecular mechanisms underlying bone cancer pain are poorly understood. Recently, T-cell death-associated gene 8 (TDAG8) has been shown to participate in complete Freund's adjuvant-induced chronic inflammatory pain. In this study, we aimed to examine whether TDAG8 and its downstream protein kinase A (PKA) pathway are involved in bone cancer pain. A bone cancer pain model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…89 Furthermore, Hang et al demonstrated GPR65 activation elicited cancer-related bone pain through the PKA and phosphorylated CREB (pCREB) signaling pathway in the rat model. 90 Collectively, GPR4, GPR65, and GPR68 are all expressed in the dorsal root ganglia; GPR65 is a functional receptor involved in nociception and the nervous system by sensitizing inflammatory pain and the evocation of cancerrelated bone pain.…”
mentioning
confidence: 99%
“…89 Furthermore, Hang et al demonstrated GPR65 activation elicited cancer-related bone pain through the PKA and phosphorylated CREB (pCREB) signaling pathway in the rat model. 90 Collectively, GPR4, GPR65, and GPR68 are all expressed in the dorsal root ganglia; GPR65 is a functional receptor involved in nociception and the nervous system by sensitizing inflammatory pain and the evocation of cancerrelated bone pain.…”
mentioning
confidence: 99%
“…Intrathecal TDAG8 siRNA attenuated bone cancer pain behaviors during the initiation and maintenance phases; there were also concomitant decreases in TDAG8 mRNA and protein levels in spinal cord. On days 6, 12 and 18 after inoculation, the relative levels of spinal TDAG8 mRNA significantly and time dependently increased in BCP rats compared to sham and NS rats [101]. The upregulation of TDAG8 protein was also demonstrated by Western blot analysis and immunohistochemistry.…”
Section: Inhibitors Of T-cell Related Proteinsmentioning
confidence: 76%
“…Knockdown of TDAG8 resulted in reduced bone cancer pain-induced spinal PKA and pCREB protein expression in two procedures. Furthermore, intrathecal H-89 (a PKA inhibitor) significantly attenuated bone cancer pain behaviors in rats [101].…”
Section: Inhibitors Of T-cell Related Proteinsmentioning
confidence: 99%
“…The regulatory subunits bind cyclic adenosine monophosphate (cAMP) and the catalytic subunits phosphorylated cAMPresponse element-binding protein (CREB) at Ser133 (Kobierski et al, 1999;Souza et al, 2011). Numerous studies have well documented that the activation of PKA signaling is involved in the modulation of nociceptive information peripheral and central sensitization produced by intense noxious stimuli (Malmberg et al, 1997;Aley and Levine, 1999;Hu et al, 2001;Hang et al, 2012Hang et al, , 2013Huang et al, 2012;Zhu et al, 2014). Moreover, several lines of evidence have shown that regulation of PKA is associated with RTK system activation (Akaneya et al, 2010;Caldwell et al, 2012).…”
Section: Introductionmentioning
confidence: 98%